Enhancing the Functional Biodiversity of Ground-Dwelling Arthropods with Henbit (Lamium amplexicaule) Conservation - Hidehiro Inagaki; Okamoto Naoya; Toyoda Yuta; Kunwar Jung (Universitas Sebelas Maret, 2025)
In European countries, considerable research has focused on the conservation and improvement of biodiversity of functional groups which are useful organisms in agricultural lands. In contrast, there is little research in this field in Asia. Living mulches using cover plants have been indicated to be an effective way to increase the density of functional groups in Europe. However, most of the living mulches used in Japan are non-native species native to Europe. There is concern that these alien plants may have a negative impact on the functional groups of native organisms. In this study, researchers investigated the impact of a community of henbit (Lamium amplexicaule), a winter weed native to Japan, on the maintenance of functional ground-dwelling arthropods. In a study of vegetable fields grown with radishes, Chinese cabbage, and onions, plastic mulch, henbit communities, and weeding areas were compared. In vegetable fields, henbit communities increased the number of functional arthropods, including carnivorous native enemies and weed seed predators, compared with plastic mulched or weeding bare ground. Weeds were removed from vegetable fields, whereas the undergrowth was often managed in tree orchards to prevent soil erosion. In a chestnut orchard study, a henbit-dominated area was compared with an area containing a mixed plant community. In the chestnut orchard, the area with henbit-dominant communities had more functional species than areas with other weed species. These results reveal that the henbit community has a positive effect on the maintenance of functional ground-dwelling arthropods.